Performing the Peace Process and Performing the Past in the Irish Republican Commemoration - Hoey, Paddy (Archīum Ateneo, 2024)
In the years since the signing of the 1998 Good Friday Peace Agreement in Northern Ireland, there has been a structural realignment of the Irish republican activist milieu. The agreement delivered the end of armed struggle for the largest republican militant group, the Provisional IRA, and provided the opportunity for the electoral growth of its formerly subordinate political wing, Sinn Féin. The latter has become the dominant gatekeeper of republican identity, defining ideologically important performative rituals, like commemorations. During the period of the Peace Process, these rituals self-consciously eschewed armed and uniformed displays of military force that were central to the propaganda war of the Troubles, such as those of the Hunger Strikes in 1981. New performative rituals of commemoration symbolized the political transformation in Provisional republicanism’s strategy. In terms of typology, rituals such as graveside orations on important commemorative dates, were reimagined to signify not military strength, but political and cultural development, with street theatre taking the place of parading and drilling. However, the peace agreement did not deliver the reunification of Ireland and the end of British rule, which had been the central aims of republican resistance. Dissident groups, who split from the Provisionals as a result of opposition to the Peace Process, have grown in support. Militant groups like the Real IRA (RIRA) have contested the internal cultural hegemony of Sinn Féin by emphasizing paramilitarist traditions at their own commemorations and funerals. By utilizing masked volunteers to deliver graveside orations and employing armed guards to fire gunshots over the coffins of dead members, they have sought to reclaim the ideologically potent performative rituals of the recent past to establish their claims to being the true keepers of republicanism’s ideological soul.